The Kappa Opioid Receptor Antagonist Aticaprant Reverses Behavioral Effects from Unpredictable Chronic Mild Stress in Male Mice - Jacobson, Moriah L. (Psychopharmacology (Berl), 2020)
RATIONALE: Major depressive disorder is a leading cause of disability worldwide and is likely precipitated by chronic stress. Although many antidepressants are currently available, these drugs require weeks to months of daily administration before reduction of symptoms occur and many patients remain treatment resistant despite several courses of treatment. There is a pressing need for new treatments for stress-related disorders. Kappa opioid receptors (KORs) are a promising new therapeutic target for MDD and anhedonia because acute KOR blockade prevents many effects of stress in rodents. OBJECTIVES: The following study assessed whether repeated treatment with the selective KOR antagonist aticaprant (also known as JNJ-67953964, and previously LY-2456302 and CERC-501) was effective in reversing behaviors in rodents following exposure to unpredictable chronic mild stress (UCMS). METHODS: Adult male C57BL/6J mice were exposed to four weeks of UCMS. After three weeks of stress, aticaprant (10 mg/kg) was administered daily for 11 treatments. Behavioral assessments included the sucrose preference test, nesting, forced swim test, hot plate test, light-dark test, and social interaction test. RESULTS: Aticaprant significantly reversed stress-induced deficits produced by UCMS on the SPT, nesting, FST, and hot plate test. The effects of aticaprant persisted through a stress and treatment recovery period. Aticaprant was not effective at reversing behavioral effects caused by stress in the light-dark and social interaction tests. CONCLUSIONS: The results support further study of the role of KORs in regulating circuits related to reward, self-care, and cognition when they are disrupted by chronic stress. They are also consistent with the clinical development of aticaprant as a therapeutic for stress-related disorders targeted at anhedonia, such as depression and post-traumatic stress disorder.